Water entry behaviour of conical projectiles - Wong, Ji Inn (2016)
This paper is a parametric study of the water-entry problem of plunging projectiles. Four nosecone shapes, namely cylindrical (flat-bottomed), conical, parabolic and power series 0.5, with variations in aspect ratio and mass, were vertically dropped from two different heights. The water entry and subsequent cavitation were captured by a high-speed camera. The projectiles were tracked, and the velocity and displacement results normalised and analysed. Comparisons were made between the projectiles at different conditions for output data of velocity, trajectory stability, cavity closure and cavity growth characteristics. It was found that the cylindrical projectiles had the lowest normalised speed but the best stability as compared to the other projectiles. The conical projectile’s velocity attenuated at a faster rate than the parabolic and power series 0.5 projectiles. Increasing the water-entry speed increased stability but decreased the normalised speed in water. A larger mass increased the stability of the projectiles as well as normalised speed, but the latter was more pronounced only for the cylindrical projectile. Lastly, increasing the aspect ratio increased the deceleration of the projectiles but provided more stability. It can be seen that trade-offs exist between velocity and trajectory stability, and the reasons can mostly be derived from the cavitation characteristics. Suggestions for improvements and future work to be done were also provided in this report.